The Gentile Mission and the Authority of Scripture in Acts - Tyson, Joseph B. 1928- (1987)
Almost all students of Luke-Acts have called attention to the special place of scripture in these documents. The fundamental Lukan strategy seems to be presented in the closing chapter of the gospel. In his post-resurrection appearance to the two disciples on the way to Emmaus, Jesus assumes the role of the authoritative interpreter of scripture and shows that it was necessary for the Christ to suffer. He interprets all the scriptures ‘beginning with Moses and all the prophets’ (Luke 24. 27; cf. 24. 35, 45). This chapter suggests to the reader that, although the scriptures are authoritative, they must be rightly, i.e. Christologically, interpreted. This widely acknowledged principle has certain implications that require investigation.